X-ray split and delay device for ultrafast x-ray science at the AMO instrument at LCLS. (November 2015) - Bozek, J D; Castagna, J C; Fang, L; Hui, Z; Kukk, E; Murphy, B F; Berrah, N
Abstract: Ultrafast molecular dynamics can be studied using x-rays from both synchrotrons sources and x-ray free electron lasers. Synchrotron studies are limited by the 10-100 ps duration pulses to processes where the Auger lifetime can be used to probe dynamics initiated by excitation of an inner-shell electron to an antibonding orbital. The short pulses produced by x-ray free electron lasers offer the opportunity to study molecular dynamics directly with pump-probe techniques. A two-mirror x-ray split and delay device has been developed for x- ray pump - x-ray probe experiments at the soft x-ray AMO instrument at the LCLS. The device operates over a photon energy range of 250-1800 eV with a variable delay of up to 200 femtoseconds with 0.1 fs resolution.